Trends in private investment in developing countries : Statistics for 1970-95 - Bouton, Lawrence (The World Bank, 1996)
This short paper, in its eighth edition, provides private and public investment data through 1995. Although the growing empirical literature on privatization has almost invariably found that the transfer of assets from public to private hands yields both efficiency and welfare gains, there has been a surprising lack of research on the macroeconomic consequences of privatization. This report addresses that issue briefly, exploring the impact of privatization on private fixed investment. As a starting point, the dimensions of the privatization revolution are summarized with special emphasis on the contribution made by foreign investors. Data on investment commitments stemming from privatization are also presented. The final section offers some econometric insights into the importance of privatization as a determinant of private investment in developing countries. The report concludes that privatization of state-owned enterprises is likely to have a multiplier effect on private investment and is, therefore, an important ingredient of governments' efforts to improve the business climate and to step up the pace of economic development. Appendix 1 discusses the methods and sources used; Appendix 2 presents tables with investment figures in terms of five ratios; Appendix 3 graphs the data by region; and Appendix 4 discusses the econometric results